PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI SMP INKLUSIF GALUH HANDAYANI SURABAYA - Sa'i, Mad; Maghfiroh, Muliatul (Rabbani: Jurnal Pendidikan Agama Islam, 2020)
Abstrak During these curriculum development has been widely discussed at the regular school level, starting from the lowest level to the top. But many of them include inclusive schools that have not been studied in curriculum development. Especially related to Islamic Education (PAI) subjects at Inclusive Middle School level. This situation will greatly affect the education system at that level starting from Educators, students, stakeholders and the community. Therefore the development of the Islamic Religious Education curriculum in Galuh Handayani Inclusive Middle School can be used as an example of a curriculum development model for the sake of advancing education in Indonesia Selama ini pengembangan kurikulum banyak dibicarakan di tataran sekolah regular mulai jenjang yang paling bawah hingga keatas. Namun banyak diantaranya sekolah inklusif yang belum diteliti pengembangan kurikulumnya. Apalagi berkaitan dengan mata pelajaran Pendidikan Agama Islam (PAI) di tingkat SMP Inklusif. Situasi ini akan sangat mempengaruhi sistem pendidikan ditingkat tersebut mulai Pendidik, peserta didik, stakeholder dan masyarakat. Oleh sebab itu pengembangan kurikulum Pendidikan Agama Islam di SMP Inklusif Galuh Handayani bisa dijadikan contoh model pengembangan kurikulum untuk kepentingan kemajuan pendidikan di Indonesia